Expression of a cDNA sequence encoding human purine nucleoside phosphorylase in rodent and human cells. - McIvor, R S (1985)
A cDNA sequence which contains the entire coding region for human purine nucleoside phosphorylase (PNP) was recombined for selection and expression in mammalian cells. Plasmids containing either the simian virus 40 early promoter or the mouse metallothionein promoter positioned just upstream of the PNP coding sequence were constructed. These plasmids also contained the gene for a methotrexate-resistant dihydrofolate reductase, allowing for selection and amplification of positive transferrents after transfection of cells by the DNA-calcium phosphate coprecipitation technique. Expression of human PNP activity was readily detected in both mouse (L) and CHO cells by isoelectric focusing of cell extracts followed by histochemical staining for PNP activity. The simian virus 40 early promoter directed considerable expression of human PNP activity in CHO cells but only scant activity in mouse cells. The mouse metallothionein promoter was not successful in effecting human PNP expression in CHO cells but provided substantial human PNP activity in mouse cells and was inducible by incubation with zinc. HeLa cell transferrents were isolated and screened for the presence of transferred PNP cDNA sequences by Southern hybridization analysis. RNA transcripts derived from the transferred PNP cDNA were identified in one of these cell lines.